Social research methods : qualitative and quantitative approaches - Neuman, W. L. (Boston : Allyn & Bacon, 2011)
Social Research Methods: Qualitative and Quantitative Methods 7e is a highly regarded text that presents a comprehensive and balanced introduction to both qualitative and quantitative approaches to social research with an emphasis on the benefits of combining various approaches.-- Publisher description.
Includes bibliographical references and indexes.
Keywords: Social sciences -- Methodology. -- Research; Sociology -- Research -- Methodology